Bail and the use of pre-trial detention: findings from an empirical study - ROGAN, MARY (My University, 2018)
This paper examines the operation of bail and the use of pre-trial detention in practice. The findings presented here come from an empirical study I have recently completed along with David Perry BL on the use of pre-trial detention in Ireland. This work was part of a cross-European study funded by the Justice Programme of the European Commission, and was also supported by the Austrian Ministry of Justice. Ireland was one of seven EU countries taking part in research on how pre-trial detention is used across the European Union. Along with ourselves, Germany, Romania, the Netherlands, Austria, Lithuania and Belgium were conducting similar research. We had two key objectives: to examine whether pre-trial detention is a measure of last resort in these countries, and to make recommendations for policy and practice. The project is known as “Pre-trial detention as ultima ratio” or DETOUR.
Criminal Law: Recent Developments and Emerging Trends
Keywords: Pre-trial detention; Justice; European Union; Ireland; Bail; Prison; Prison Law; accountability in prisons; human rights in prison; prison oversight; prison policy; prison policy in ireland; Policy